Improved adenoma detection with Endocuff Vision: the ADENOMA randomised controlled trial. Issue 2 (23rd January 2018) - Ngu, Wee Sing; Bevan, Roisin; Tsiamoulos, Zacharias P; Bassett, Paul; Hoare, Zoë; Rutter, Matthew D; Clifford, Gayle; Totton, Nicola; Lee, Thomas J; Ramadas, Arvind; Silcock, John G; Painter, John; et al.
Abstract : Objective: Low adenoma detection rates (ADR) are linked to increased postcolonoscopy colorectal cancer rates and reduced cancer survival. Devices to enhance mucosal visualisation such as Endocuff Vision (EV) may improve ADR. This multicentre randomised controlled trial compared ADR between EV-assisted colonoscopy (EAC) and standard colonoscopy (SC). Design: Patients referred because of symptoms, surveillance or following a positive faecal occult blood test (FOBt) as part of the Bowel Cancer Screening Programme were recruited from seven hospitals. ADR, mean adenomas per procedure, size and location of adenomas, sessile serrated polyps, EV removal rate, caecal intubation rate, procedural time, patient experience, effect of EV on workload and adverse events were measured. Results: 1772 patients (57% male, mean age 62 years) were recruited over 16 months with 45% recruited through screening. EAC increased ADR globally from 36.2% to 40.9% (P=0.02). The increase was driven by a 10.8% increase in FOBt-positive screening patients (50.9% SC vs 61.7% EAC, P<0.001). EV patients had higher detection of mean adenomas per procedure, sessile serrated polyps, left-sided, diminutive, small adenomas and cancers (cancer 4.1% vs 2.3%, P=0.02). EV removal rate was 4.1%. Median intubation was a minute quicker with EAC (P=0.001), with no difference in caecal intubation rate or withdrawal time. EAC was well tolerated but caused a minor increase in discomfort on anal intubation in patients undergoing colonoscopy with no or minimal sedation. There were no significant EV adverse events. Conclusion: EV significantly improved ADR in bowel cancer screening patients and should be used to improve colonoscopic detection. Trial registration number: NCT02552017, Results; ISRCTN11821044, Results.